2022
DOI: 10.1038/s41433-022-01961-3
|View full text |Cite
|
Sign up to set email alerts
|

Global metrics on ocular biometry: representative averages and standard deviations across ten countries from four continents

Abstract: Background/Objectives We provide global averages and standard deviations for ocular biometry—axial length (AL), corneal radius of curvature (CR), anterior chamber depth (ACD), lens thickness (LT), white to white (WTW), and central corneal thickness (CT). We hope a better understanding of normal and abnormal values will help clinicians gain further insight into their surgical outcomes, especially for off-target eyes. Subjects/Methods We searched the MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Since the corneal and CL thickness are usually recorded in the same magnitudes (mm), the sample size calculation was based on this parameter. Previous reports indicate that the mean SDs of CCT are usually distributed with a value of 38 mm, 20 whereas the lowest value of the CL thickness used in this study was 80 mm (Table 1). Based on those data, to have 90% power (type II error associated) for a significance level of ?¼0.05 (type I error associated) with a confidence level of 95% to detect a clinical difference between values with and without CL, the minimum number of subjects required was six per group; since two different CLs were used in a paired analysis, a minimum of 12 participants are needed in the final study group to avoid statistical interference.…”
Section: Sample Size Calculation Inclusion and Exclusion Criteria And...mentioning
confidence: 51%
“…Since the corneal and CL thickness are usually recorded in the same magnitudes (mm), the sample size calculation was based on this parameter. Previous reports indicate that the mean SDs of CCT are usually distributed with a value of 38 mm, 20 whereas the lowest value of the CL thickness used in this study was 80 mm (Table 1). Based on those data, to have 90% power (type II error associated) for a significance level of ?¼0.05 (type I error associated) with a confidence level of 95% to detect a clinical difference between values with and without CL, the minimum number of subjects required was six per group; since two different CLs were used in a paired analysis, a minimum of 12 participants are needed in the final study group to avoid statistical interference.…”
Section: Sample Size Calculation Inclusion and Exclusion Criteria And...mentioning
confidence: 51%
“…The results of recent studies presented significant racial differences. Studies from Asian and Hispanic populations have presented longer axial length than European populations [ 33 ]. All patients in our study were of European origin, [ 23 ] and our biometric results are the closest to those from Germany [ 7 ] and Slovakia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, disparity in the type of instrument used for the measurement could have influenced the result recorded like use of A scans were reported to have a shorter axial length when compared to the use of optical low-coherence reflectometry, which gives longer Als. [19] Moreover, variations in the size of globes for males and females of other races including Caucasians and African which is not the case in Asians (Japanese, Chinese) could be the reason for the longer AL measured among males than females. [20] The steeper corneal curvature and smaller WTW corneal diameter recorded in the current study among females are expected, as taller people are reported to have longer eyes, deeper anterior chamber depths, and flatter corneal curvature radii.…”
Section: Discussionmentioning
confidence: 99%